2021
DOI: 10.1108/acmm-12-2020-2417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper addition in carbon steel on biocorrosion by sulfate-reducing bacteria in solution

Abstract: Purpose This paper aims to investigate the anti-biocorrosion performance and mechanism of the Cu-bearing carbon steel in the environment containing sulfate-reducing bacterial (SRB). Design/methodology/approach The biocorrosion behavior of specimens with Cu concentration of 0 Wt.%, 0.1 Wt.%, 0.3 Wt.% and 0.6 Wt.% were investigated by immersion test in SRB solution. By examining the prepared cross-section of the biofilm using focused ion beam microscopy, SRB distribution, bacterial morphology, biofilm structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The result is different from our present and previous studies. [12][13][14]19) Yu et al 16,17) and Huang et al 20) also reported that the Cu-bearing carbon steel exhibited strong antibacterial activity against SRB. This is also confirmed recently by study of Fan et al 22) Their results showed that MIC resistance of the Cu-bearing pipeline steel was better than those of X70 and Cr-bearing steels.…”
Section: Corrosion Against Srb Of Cu/ni-added Steelmentioning
confidence: 99%
See 2 more Smart Citations
“…The result is different from our present and previous studies. [12][13][14]19) Yu et al 16,17) and Huang et al 20) also reported that the Cu-bearing carbon steel exhibited strong antibacterial activity against SRB. This is also confirmed recently by study of Fan et al 22) Their results showed that MIC resistance of the Cu-bearing pipeline steel was better than those of X70 and Cr-bearing steels.…”
Section: Corrosion Against Srb Of Cu/ni-added Steelmentioning
confidence: 99%
“…To solve the MIC trouble of pipelines used in oil/gas exploitation and transportation, various mitigation countermeasures such as physical and chemical approach, 7) protective coatings, 8,9) biological competition, 10,11) and antibacterial steel pipe have been developed. [12][13][14][15][16][17][18][19][20][21][22] Among them, antibacterial steel pipe is a new strategy to mitigate MIC from the aspect of material itself, having the characteristics of long-term durability. [12][13][14] By proper Cu alloying design to the traditional pipeline steels, aiming at continuous release of Cu ions to kill the bacteria and inhibit the formation of bacterial biofilm, a creative strategy for improving the MIC resistance of pipeline steels has been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, some environmentally friendly corrosion inhibitors have attracted a lot of attention, such as benzotriazole (BTA, C 6 H 5 N 3 ) (Xiong et al , 2022), 8-hydroxyquinoline (C 9 H 7 NO), 2-mercaptobenzothiazole (C 7 H 5 NS 2 ) and some other natural product inhibitors (Ma et al , 2022). Capsaicin derivatives (CAP, C 18 H 27 NO 3 ), isothiazolinone derivatives (C 11 H 17 C l2 NOS) and quinoline alkaloids (C 20 H 16 N 2 O 4 ) extracted from pepper have significant effects on the prevention and control of marine biological corrosion and will not cause any impact on marine ecology (Gabe et al , 2021; Hao et al , 2020; Yu et al , 2022). However, the direct addition of a corrosion inhibitor to the coating will cause an explosion in the early stages, leaving holes in the coating, resulting in a serious decline in the later anticorrosion efficiency (Zuo et al , 2019).…”
Section: Introductionmentioning
confidence: 99%